Keanekaragaman Ektoparasit di Peternakan Sapi Potong Astomulyo Lampung Tengah dan Peternakan Sapi Perah Kawasan Usaha Peternakan Rakyat (KUNAK) Bogor - Shodiq, Nadim; Supriyono, Supriyono; Pisestyani, Herwin (JURNAL KAJIAN VETERINER, 2025)
Ectoparasites in livestock areas can cause losses to farmers, such as decreased body weight and milk production due to anemia, disease transmission, and animal discomfort. This study aimed to identify the diversity, abundance, and potential risk of diseases that can be transmitted by ectoparasites as disease vectors in cattle. The study was conducted in two selected locations: Astomulyo beef cattle farm in Central Lampung and KUNAK dairy farm in Bogor. All ectoparasites around the pens were collected using sweep nets, aspirators, light traps and forceps. Identification results showed a diverse range of ectoparasites, including mosquitoes (Culicidae), flies (Muscidae), ticks (Haemaphysalis), Culicoides (Ceratopogonidae) and fleas (Haematopinidae). The environment, such as pens conditions, storage facilities, manure management, feed waste, and sanitation, influenced the diversity of ectoparasite species found in the study sites. The identified ectoparasite species have the potential to be vectors of various livestock diseases that lead to decreased production. This study is expected to provide information related to effective disease prevention and control strategies.